DEVELOPING AN ECOLOGICAL CURRICULUM FOR ENGLISH LANGUAGE LEARNERS - Rustamova Adash Eshankulovna; Musurmonova Saodat Jamshidovna (TADQIQOTLAR, 2025)
Developing  an  ecological  curriculum  for  English  Language  Learners  (ELLs) involves integrating environmental education with language learning. This approach not  only  helps  students  improve  their  English  skills  but  also  raises  awareness  of ecological issues and fosters a sense of stewardship for the environment. Ecological curriculum  goals  and  objectives  includes  language  proficiency:  enhance  listening, speaking,  reading,  and  writing  skills  in  English,  environmental  awareness:  foster understanding of key ecological concepts and issues (e.g., biodiversity, climate change, sustainability),  cultural  connections:  explore  local  ecosystems  and  cultural perspectives on environmental issues. Within the life domains, the educational team identifies  the  environments  where  it  is  most  desirable  for  the  student  with  severe disabilities  to  participate.  The  student's  current  home,  school,  and  community environments  are  considered,  and  particular  attention  is  placed  on  integrated  or "typical"  environments  used  by  peers  without  disabilities,  even  if  the  integrated environments  are  not  currently  used  by  or  available  to  the  student.  Following  are considerations for each environment: